Volume 4: 36th Mechanisms and Robotics Conference, Parts a and B 2012
DOI: 10.1115/detc2012-71514
|View full text |Cite
|
Sign up to set email alerts
|

The Scope for a Compliant Homokinetic Coupling Based on Review of Compliant Joints and Rigid-Body Constant Velocity Universal Joints

Abstract: Many applications require a compliant mechanism to transmit rotation from one direct to another direct with constant velocity. This paper presents a literature survey towards the design of compliant constant velocity universal joints. The traditional constant velocity universal joints available from the literature were studied, classified and their mechanical efficiencies were compared. Also the graph representation of them was studied. In the same manner, literature review for different kind of compliant join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The axis drift is of little importance, since the manipulator will use the environment to bend around its objects. By comparing the data of different compliant rotational joints found in the article by Machekposhti et al (2012) and Trease et al (2005), the cross axis joint shown in Fig. 1a was used in our study.…”
Section: The Compliant Jointmentioning
confidence: 99%
“…The axis drift is of little importance, since the manipulator will use the environment to bend around its objects. By comparing the data of different compliant rotational joints found in the article by Machekposhti et al (2012) and Trease et al (2005), the cross axis joint shown in Fig. 1a was used in our study.…”
Section: The Compliant Jointmentioning
confidence: 99%
“…By comparing the data of different compliant rotational joints found in the article by Machekposhti et al (2012) and Trease et al (2005), the cross axis joint shown in Fig. The lateral stiffness has to be high enough in order for the manipulator to not bend downwards in the lateral plane (due to its own weight).…”
Section: The Compliant Jointmentioning
confidence: 99%
“…The spatial freedom in additive manufacturing (AM) produces parts in a single step by repeated layer-wise addition of a metallic or polymer material [6]. The "free complexity" of AM enables three-dimensional (3D) and complex CEs (usually the combination of simpler or more complex CEs [7][8][9]) that were previously too complicated to fabricate using traditional manufacturing processes [10], including computer-controlled numerical (CNC) milling, wire electrical discharge machining (EDM), or laser cutting, in which the material is continuously machined out of bulk material. Several spatial additive manufactured mechanisms were demonstrated using polymer-based AM techniques such as material extrusion [11][12][13][14], selective laser sintering [15][16][17], or vat photopolymerization [18][19][20].…”
Section: Introductionmentioning
confidence: 99%